2016 FINRA analysis: a record-breaking year for fines. Issue 2 (3rd July 2017) - Rubin, Brian; Pollet, Adam
Abstract : Purpose: To analyze FINRA's 2016 sanctions and cases, the issues that resulted in the most significant fines, emerging enforcement trends, and make predictions about key issues for FINRA for 2017 and beyond. Design/methodology/approach: Discusses the sanctions and disciplinary actions in 2016 and prior years; details the top 2016 enforcement issues measured by total fines assessed, including anti-money laundering, variable annuities, trade reporting, books and records, and unregistered securities; explains current enforcement trends, including fines of 1 million or more, sanctions against compliance officers, and suitability cases; and analyzes three enforcement topics that will likely continue to receive heightened attention from FINRA in 2017 and beyond: restitution, cybersecurity, and senior investors. Findings: The fines ordered by FINRA in 2016 reached an all-time high while the amount of restitution ordered and the number of disciplinary actions remained on par with prior years. Practical implications: Firms and their representatives should heed the trends in both the substantial fines FINRA is ordering and the related enforcement issues in the cases FINRA has brought. Originality/value: Expert analysis and guidance from experienced securities enforcement lawyers.